Prospects for the Development of a Dengue Vaccine - Usa Thisyakorn; Chule Thisyakorn (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Dengue is a mosquito-borne viral disease which is currently an important and rapid growing health problem across the globe. Four closely related dengue serotypes cause the disease, which ranges from asymptomatic infection to undifferentiated fever, dengue fever (DF), and dengue hemorrhagic fever (DHF). Specific antiviral medications are not available for dengue and successful treatment, which is mainly supportive, depends on early recognition of the disease and careful monitoring for shock. Prevention of dengue depends on the control of the mosquito vector which has had only limited success. Development of a dengue vaccine is seen as a new tool to prevent this potentially fatal disease. The scope and intensity of dengue vaccine development has increased dramatically in the last decade. A live-attenuated tetravalent dengue vaccine based on chimeric yellow fever dengue virus, has progressed to licensure in several dengue endemic countries in 2015 after its phase III efficacy study involving more than 30,000 volunteers from Asia and Latin America. Several other dengue vaccine candidates are currently being evaluated in clinical and preclinical studies included other live attenuated vaccines, subunit, DNA purified inactivated vaccine candidates as well as virus-vectored and virus-like particle-based vaccines. Since dengue poses a heavy  conomic cost to the health system and society, the potential economic benefits are associated with promising dengue prevention interventions such as dengue vaccine and vector control innovations.